2017
DOI: 10.2119/molmed.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

IL-37 Suppresses MyD88-mediated Inflammatory Responses in Human Aortic Valve Interstitial Cells

Abstract: Calcific aortic valve disease (CAVD) is common among the elderly, and aortic valve interstitial cells (AVICs) exhibit unique inflammatory and osteogenic responses to proinflammatory stimulation, which plays an important role in valvular fibrosis and calcification. Thus, suppression of AVIC proinflammatory response may have therapeutic utility for the prevention of CAVD progression. Interleukin (IL)-37, an antiinflammatory cytokine, reduces tissue inflammation. This study aimed to test the hypothesis that IL-37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…The first association of viral-derived molecules with inflammation and calcification of human VIC through TLR3 was reported using polyinosinic acid: polycytidylic acid to mimic dsRNA effects (López et al, 2012 ). Zhan et al, later confirmed dsRNA-mediated up-regulation of inflammatory mediators and pro-osteogenic activity, and further demonstrated by gene-silencing and neutralizing antibodies the involvement of TLR3-TRIF non canonical NF-κB signaling pathways as well as the ERK route (Zhan et al, 2015 , 2017 ). Moreover, recent in vivo data presented at European Society of Cardiology Congress 2017 have associated TLR3 to the onset of calcific aortic valve disease by using TLR3- and ApoE-deficient mice models (Tepekoylu et al, 2017 ).…”
Section: Tlr and Cavd Pathogenesismentioning
confidence: 94%
“…The first association of viral-derived molecules with inflammation and calcification of human VIC through TLR3 was reported using polyinosinic acid: polycytidylic acid to mimic dsRNA effects (López et al, 2012 ). Zhan et al, later confirmed dsRNA-mediated up-regulation of inflammatory mediators and pro-osteogenic activity, and further demonstrated by gene-silencing and neutralizing antibodies the involvement of TLR3-TRIF non canonical NF-κB signaling pathways as well as the ERK route (Zhan et al, 2015 , 2017 ). Moreover, recent in vivo data presented at European Society of Cardiology Congress 2017 have associated TLR3 to the onset of calcific aortic valve disease by using TLR3- and ApoE-deficient mice models (Tepekoylu et al, 2017 ).…”
Section: Tlr and Cavd Pathogenesismentioning
confidence: 94%
“…IL‐1 family plays a crucial role in the regulation of immune and inflammatory responses to several antigens which can be inhibited by IL‐1 inhibitors such as IL‐37 and IL‐1 receptor antagonist (IL‐1RA), a natural inhibitor of IL‐1 (Garlanda, Dinarello, & Mantovani, ). Binding IL‐1 receptor (IL‐1R) by antigens provokes an activation of MyD88 pathway which leads to NF‐κB and, therefore, to the inflammatory cytokine gene expression (Zhan et al, ; Table ).…”
Section: Interleukin‐18mentioning
confidence: 99%
“…Receptor-activated mast cells lead to the generation of inflammatory compounds which mediate psoriasis inflammation. Cytokines IL-37, IL-10, and TGF-beta are potential inhibitors of the inflammatory response Binding IL-1 receptor (IL-1R) by antigens provokes an activation of MyD88 pathway which leads to NF-κB and, therefore, to the inflammatory cytokine gene expression (Zhan et al, 2017; Table 1).…”
Section: Interleukin-18mentioning
confidence: 99%
“…In addition to studies in IL-37 transgenic mice, the extracellular function of IL-37 using recombinant IL-37 inhibits inflammation in vitro and in vivo in wild-type (WT) mice (12)(13)(14)(15)(16)(17)(18). Recombinant IL-37 improves insulin sensitivity and reduces inflammatory cytokine production in adipose tissue (13), ameliorates joint and systemic inflammation (15), limits the metabolic costs of chronic inflammation, which promotes exercise tolerance (14), and promotes intestinal immune homeostasis (19).…”
mentioning
confidence: 99%